Multiple intracranial meningiomas: diagnosis, biological behavior and treatment Meningiomas intracranianos múltiplos: diagnóstico, comportamento biológico e tratamento - José Carlos Lynch; Leandro Alcy Sales Ferreira; Leonardo Welling; Renata Cardoso Schulz (Arquivos de Neuro-Psiquiatria)
Multiple intracranial meningiomas (MIM) are a rare pathology when not associated with neurofibromatosis. The prevalence rate of those tumors varied from 2.3 to 8.9% of all intracranial meningiomas. OBJECTIVE: To present, analyze and discuss the cases of seven patients diagnosed with multiple intracranial meningiomas, describing their clinical and histological characteristics, as well as their biological behavior. METHOD: The patients records, surgical descriptions, imaging studies and the histopathological exams were retrospectively reviewed. This is the largest series of MIM publisted in Brazil. RESULTS: This sample consists of five women and two men. The age varied from 42 to 84 (average 53.8). Twenty-two meningiomas were identified and varied from 1.5 to 192 cm³, with an 62.8 cm³ average volume. The number of procedures varied from 1 to 5 per patient. No surgical death occurred in this series. CONCLUSION: Despite the multiplicity of tumors, number of recurrences, the new tumors, repeated operations and re-operations, radiotherapy and a number of postoperative complications, the patients experienced a long survival in conjunction with a fairly good quality of life. Os meningiomas intracranianos múltiplos são tumores raros quando não associados a neurofibromatose, correspondem de 2,3 a 8,9% de todos os meningiomas intracranianos. OBJETIVO: Apresentar, analisar e discutir 7 pacientes com diagnóstico de meningioma intracraniano múltiplo, descrevendo as características clínicas, histológicas e o comportamento biológico desses tumores. MÉTODO: Trata-se de revisão retrospectiva incluindo a análise dos prontuários, das descrições cirúrgicas, dos estudos de imagem e do material histopatológico. Esta série é a maior série de meningiomas intracranianos múltiplos publicada no Brasil. RESULTADOS: A casuística é composta de 5 mulheres e 2 homens. A idade oscilou entre 42 e 84 anos, com média de 53,8 anos. Identificamos 22 meningiomas que variaram de 1,5 a 192 cm³, com volume médio de 62,8 cm³. O número de procedimentos oscilou de 1 a 5 por paciente. Não ocorreu mortalidade cirúrgica. CONCLUSÃO: Apesar de vários tumores, de recorrências, do surgimento de novas neoplasias, de várias cirurgias, re-operações, do tratamento com radioterapia e de inúmeras complicações pós-operatórias, esses pacientes obtiveram uma longa sobrevida com boa qualidade de vida.